Sex-dependent neurochemical effects of environmental enrichment in the visual system - Bessinis, D P; Dalla, C; Kokras, N; Pitychoutis, P M; Papadopoulou-Daifoti, Z. (Neuroscience, 2013)
Sex differences in the visual system have been reported in aspects of human vision, such as color perception, peripheral vision and even in the activation of the primary visual cortex. Similarly sex differences have been identified in the visual system of laboratory animals such as monkeys and rats. On the other hand, environmental enrichment (EE) has long been known to affect visual tissues. Taking into consideration the variation in the experimental approaches concerning EE and the sex differences in the visual system, we investigated in male and female rats the serotonergic and dopaminergic effects of EE in the retina and the visual cortex at different time points (i.e. P0-25, P0-P90 and P90-P150). Early EE in adulthood increased the serotonergic activity of the male visual cortex and the female retina (P0-P90). In addition early enrichment (P0-P90) increased dopaminergic activity in the female retina and in the visual cortex of both sexes. Late enrichment increased the serotonergic activity in the retina and visual cortex of both sexes (P90-P150), but increased the dopaminergic activity in the visual cortex only in male animals. In the present study we expose marked sex differences in the neurochemistry of visual tissues and we demonstrate for the first time that EE can in fact modify the serotonergic and dopaminergic neurotransmission in the retina and visual cortex. Overall, the present study underpins the sex-dependent neurochemical status of the visual system and provides insights into the different mechanisms underlying visual processing in the two sexes.
Keywords: *Environment; *Sex Characteristics; 3,4 dihydroxyphenylacetic acid; 3,4-Dihydroxyphenylacetic Acid/analysis/metabolism; 5-hiaa; 5-ht; 5-hydroxyindoleacetic acid; Analysis of Variance; Animals; Anova; Da; Dopac; Dopamine; Dopamine/analysis/metabolism; Ee; enriched environment; environmental enrichment; Female; high-performance liquid chromatography; Homovanillic Acid; HPLC; Hva; Hydroxyindoleacetic Acid/analysis/metabolism; Male; Rats; Rats, Wistar; Retina; Retina/chemistry/*metabolism; Serotonin; Serotonin/analysis/metabolism; Sex differences; Visual Cortex; Visual Cortex/chemistry/*metabolism; Visual Pathways/chemistry/*metabolism